Spanish national narrative in secondary education: Reconquest, Catholic Monarchs and Empire in history textbooks and students’ accounts - Sáiz Serrano, Jorge (Historia y Memoria de la Educación, 2017)
This paper examines the survival of a master narrative about the history of Spain, a national narrative as it is reflected in history textbooks in secondary education between 1976 and 2016 and in current historical accounts of students and teachers-in-training. The aim is to analyze three subjects of this master narrative (the Reconquest, the Catholic Monarchs and the Spanish Empire) that continue to have their place in history textbooks. We analyze the contents and forms of discourse with this aim: to demonstrate to what extent the political, educational and historiographical changes have transformed the national historical representation of such contents as a national discourse. This is an empirical, exploratory and descriptive study based on discourse analysis using a probability sample from history textbooks. This analysis is then compared with studies on historical accounts of Spain given by students and teachers-in-training. The results show a duality between textbooks and historical accounts of adolescents and youth. On the one hand, we see significant changes in academic texts from school textbooks without an essentialist national dimension; but we also see continuity in the discursive thread of the master narrative (reconquest-unit-empire), and with maps of «Spain» from the 16th century and with images of national historical painting from the nineteenth century. On the other hand, we can see the continuity of essentialist and traditional representations of such contents in historical accounts of students and teachers-in-training. This is due principally to poor historical literacy in secondary education and the survival of a national master narrative in non-school social uses of the national historical past.